A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Simplify: 5x  6y + 4x
anonymous
 one year ago
Simplify: 5x  6y + 4x

This Question is Open

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Simplifying 5x + 6y + 4x = 0 Reorder the terms: 5x + 4x + 6y = 0 Combine like terms: 5x + 4x = 9x 9x + 6y = 0 Solving 9x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 9x + 6y + 6y = 0 + 6y Combine like terms: 6y + 6y = 0 9x + 0 = 0 + 6y 9x = 0 + 6y Remove the zero: 9x = 6y Divide each side by '9'. x = 0.6666666667y Simplifying x = 0.6666666667y
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.